Solvent‐Free Synthesis of ITQ‐12, ITQ‐13, and ITQ‐17 Zeolites. Issue 5 (1st March 2017) - Wu, Qinming; Liu, Xiaolong; Zhu, Longfeng; Meng, Xiangju; Deng, Feng; Fan, Fengtao; Feng, Zhaochi; Li, Can; Maurer, Stefan; Feyen, Mathias; Müller, Ulrich; Xiao, Feng‐Shou
Abstract: Development of the sustainable routes for synthesis of ITQ‐family zeolites is very important because of their unique structures and excellent catalytic and adsorptive properties. The burden of costly raw materials and low efficiency of synthesis put a strong challenge for their widespread commercial application. Here, we show an alternative and simple route for synthesis of ITQ‐12, ITQ‐13, and ITQ‐17 zeolites using commercially available organic templates by a facile grinding process of anhydrous starting raw solids, followed by heating at 140—180 °C. Compared with the conventional hydrothermal synthesis, this approach has obvious advantages such as employment of low‐cost organic templates with very high effectiveness, high yield of zeolite products, short crystallization time, and relatively simple procedures. This methodology might open a pathway to synthesize ITQ zeolites with more sustainable manner. Abstract : Solvent‐free route for synthesizing ITQ‐12, ITQ‐13, and ITQ‐17 zeolites has been designed using low‐cost organic templates by a facile grinding process of anhydrous starting raw solids, followed by heating at 140—180 °C. This methodology opens a pathway to synthesize ITQ zeolites with more sustainable manner.